APLIKASI MULTIPLE MEDIA PLAYER (AUDIO-VIDEO) UNTUK COMPATIBLE TERHADAP SISTEM OPERASI WINDOWS - Khairil, Khairil; Sapri, Sapri; Trianggana, Dimas Aulia (UNIVED Press, 2013)
The purpose ofwriting this thesisis to designandcreate an applicationvideomediaplayer thatcan read/playbackvideoplayerwithout having tolook forthe completenessof theapplication ofvideomediaplayer. Benefits thatcanbe takentodesign and makeavideomediaplayersoftwarethatcan read/playbackvideoplayerwithout having tolook forthe completenessof the applicationvideomediaplayer. Can becomeanadvanced researchandbe a referenceforother research. Penelitinandtestresultscan be concludedas follows.Multiple Video Player application can be created using Visual Basic 6.0 programming language.This application isused torotate theVideoPlayer withVideoPlayerFormatasfollows, DVD is byformatvideoDAT, AllFormatsVideoAsFLV, 3GP, MPEG, MP4,MKV,AVIThattheFlash PlayerSWFvideoformat.